2016
DOI: 10.1080/09540121.2016.1159651
|View full text |Cite
|
Sign up to set email alerts
|

“It's because they care”: understanding pathways to classroom concentration problems among HIV-affected children and youth in Western Kenya

Abstract: Children and young people living in households affected by HIV are experiencing poorer educational outcomes compared to their peers. This article explores how different forms of marginalisation interface and manifest themselves in classroom concentration problems, undermining their education. This mixed qualitative methods study was conducted with teachers and pupils from three primary and three secondary schools in the Siaya County of Western Kenya. Specifically, it involved 18 teachers through individual int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…A study from Namibia and Swaziland [18] reported that schools generally did not meet HEU children's needs and most of them dropped out of school due to teachers' violent behavior and ostracism from their teachers and peers. In addition, social issues such as bullying, discrimination, and stigma for HIV families were very frequent, and teachers also confirmed that those were among the main causes for dropping out of school [18] Studies from Kenya and Zimbabwe [23,62] showed that the lack of supportive adults, household responsibilities, and child abuse and neglect impacted school attendance in HIVaffected children. In particular, the qualitative study from Kenya [23] collected teachers' interviews, which mostly explained that pupils had to provide medicine and food for their HIV-sick parents every day.…”
Section: Social Factors and School Environment Risk And Protective Fa...mentioning
confidence: 98%
See 2 more Smart Citations
“…A study from Namibia and Swaziland [18] reported that schools generally did not meet HEU children's needs and most of them dropped out of school due to teachers' violent behavior and ostracism from their teachers and peers. In addition, social issues such as bullying, discrimination, and stigma for HIV families were very frequent, and teachers also confirmed that those were among the main causes for dropping out of school [18] Studies from Kenya and Zimbabwe [23,62] showed that the lack of supportive adults, household responsibilities, and child abuse and neglect impacted school attendance in HIVaffected children. In particular, the qualitative study from Kenya [23] collected teachers' interviews, which mostly explained that pupils had to provide medicine and food for their HIV-sick parents every day.…”
Section: Social Factors and School Environment Risk And Protective Fa...mentioning
confidence: 98%
“…In addition, social issues such as bullying, discrimination, and stigma for HIV families were very frequent, and teachers also confirmed that those were among the main causes for dropping out of school [18] Studies from Kenya and Zimbabwe [23,62] showed that the lack of supportive adults, household responsibilities, and child abuse and neglect impacted school attendance in HIVaffected children. In particular, the qualitative study from Kenya [23] collected teachers' interviews, which mostly explained that pupils had to provide medicine and food for their HIV-sick parents every day. Moreover, if caregivers were bedridden, they also had to take care of their basic needs, such as hygiene.…”
Section: Social Factors and School Environment Risk And Protective Fa...mentioning
confidence: 98%
See 1 more Smart Citation
“…(Sad face with tears in the eyes.) (P10, female, 25 years old, college student) Skovdal 35 asserts that a child or young person who has experienced HIV/AIDS-related issues is likely to have low educational achievements. These children struggle to focus in class, which lowers their grades, causes them to miss class frequently, or even quit school altogether.…”
Section: Consequences Of Death While Siblings Are Still At Schoolmentioning
confidence: 99%
“…Goldberg and Short ( 2016 ) explore whether Kenyan mothers in HIV-affected households were willing to foster homeless children. HIV can disrupt functioning in many ways and the paper by Skovdal ( 2016 ) explores why HIV-affected children have classroom concentration problems and consequently poorer educational outcomes. Hensels et al ( 2016 ) focus on gender differences in children attending community-based organisations in Malawi and South Africa, highlighting that for younger children there are many similarities across the gender divide, but when there are differences, it is boys who are disadvantaged and overlooked – perhaps prompting the equity needs of boys to be maintained, although girls have often been the target of interventions.…”
mentioning
confidence: 99%